Fire-resistant resin composition

The fire-resistant resin composition addresses issues of brittleness and inconsistent performance by optimizing the ratio and content of thermally expandable graphite and inorganic filler, enhancing fire resistance and mechanical strength through improved dispersibility and stability.

JP2025010220AActive Publication Date: 2025-01-20SEKISUI CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024188367
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2016-11-28
Filing Date
2024-10-25
Publication Date
2025-01-20
Estimated Expiration
2037-01-27

AI Technical Summary

Technical Problem

Existing fire-resistant resin compositions using thermally expandable graphite face issues such as decreased expansion ratio, brittleness, surface staining, and inconsistent fireproof performance due to insufficient kneading and high inorganic filler content, leading to handling difficulties and variations in fireproofing effectiveness.

Method used

A fire-resistant resin composition is formulated with a particle size ratio of thermally expandable graphite to inorganic filler between 1 to 1000 and a total content of 30% by weight or more, incorporating thermally expandable graphite at 5% by weight or more, along with specific additives like phosphite and polyphosphate, to enhance dispersibility and stability.

Benefits of technology

The composition achieves excellent fire retardancy, surface finish, and strength, ensuring consistent fire resistance and improved mechanical properties while maintaining efficient kneading and dispersibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010220000006
    Figure 2025010220000006
  • Figure 2025010220000001
    Figure 2025010220000001
  • Figure 2025010220000002
    Figure 2025010220000002
Patent Text Reader

Abstract

To provide a fire-resistant resin composition excellent in flame retardancy and also excellent in surface finish and strength.SOLUTION: The fire-resistant resin composition contains: a matrix component which is a resin, an elastomer, a rubber, or a combination thereof; thermally expandable graphite; and an inorganic filler. The particle diameter ratio of the particle diameter of the thermally expandable graphite to the particle diameter of the inorganic filler is in the range of 1-1,000. The total content of the thermally expandable graphite and the inorganic filler is 30 wt.% or more. The content of the thermally expandable graphite is 5 wt.% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fire-resistant resin composition. [Background technology]

[0002] Resin materials containing thermally expandable graphite have been proposed as fire-resistant resin materials for use in the construction field (Patent Documents 1 to 4).

[0003] However, fireproof materials containing thermally expandable graphite need to be processed for a short time, otherwise the components in the thermally expandable graphite will escape and the expansion ratio will decrease. On the other hand, fireproof materials often contain a lot of inorganic fillers and flame retardants in addition to the thermally expandable graphite, and they need to be thoroughly kneaded to mix them into the binder resin. If the kneading is insufficient, the fireproof material will become brittle, the surface will become dirty (powdering or blackening), and handling will be difficult. In addition, the fireproof performance may vary depending on the sampling position of the fireproof material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 9-227716 [Patent Document 2] Patent Publication No. 9-227747 [Patent Document 3] Patent Publication No. 10-95887 [Patent Document 4] Patent Publication No. 2000-143941 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a fire-resistant resin composition which has excellent expandability, stably exhibits fire resistance, and is also excellent in surface finish and strength. [Means for solving the problem]

[0006] In order to achieve the above object, the present inventors have discovered that the above problems can be solved by making the particle size ratio of the particle size of the thermally expandable graphite to the particle size of the inorganic filler in a fire-resistant resin composition from 1 to 1000, the total content of the thermally expandable graphite and the inorganic filler to 30% by weight or more, and the content of the thermally expandable graphite to 5% by weight or more, and have thus completed the present invention.

[0007] The present invention includes the following aspects.

[0008] Item 1. A fire-resistant resin composition containing a matrix component which is a resin, an elastomer, a rubber, or a combination thereof, thermally expandable graphite, and an inorganic filler, A fire-resistant resin composition, characterized in that the particle size ratio of the thermally expandable graphite to the inorganic filler is in the range of 1 to 1000, the total content of the thermally expandable graphite and the inorganic filler is 30% by weight or more, and the content of the thermally expandable graphite is 15% by weight or more.

[0009] Item 2: A fire-resistant resin composition containing a matrix component which is a resin, an elastomer, a rubber, or a combination thereof, thermally expandable graphite, and an inorganic filler, A fire-resistant resin composition, characterized in that the particle size ratio of the thermally expandable graphite to the inorganic filler is in the range of 1 to 1000, the total content of the thermally expandable graphite and the inorganic filler is 30% by weight or more, and the content of the thermally expandable graphite is 5% by weight or more.

[0010] Item 3. The fire-resistant resin composition according to item 1 or 2, wherein the average particle size of the thermally expandable graphite is 100 μm or more.

[0011] Item 4. The fire-resistant resin composition according to any one of Items 1 to 3, wherein the inorganic filler contains a phosphite.

[0012] Item 5. The fire-resistant resin composition according to any one of Items 1 to 4, further comprising a polyphosphate.

[0013] Item 6. The fire-resistant resin composition according to any one of Items 1 to 5, further comprising a plasticizer.

[0014] Item 7. The fire-resistant resin composition according to any one of Items 1 to 6, wherein the matrix component is a vinyl chloride resin or a polyolefin resin.

[0015] Item 8. A fire-resistant resin molding comprising the fire-resistant resin composition according to any one of items 1 to 7.

[0016] Item 9. A fitting comprising the fire-resistant resin molding according to item 8. Effect of the Invention

[0017] According to the present invention, there is provided a fire-resistant resin composition which is excellent in flame retardancy, surface finish and strength. [Brief description of the drawings]

[0018] [Figure 1] 1 is a schematic front view showing a fire-resistant window having a sash frame provided with a fire-resistant resin molded article made of the fire-resistant resin composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described.

[0020] The matrix component may be any of a resin, an elastomer, and a rubber. Resins include thermoplastic resins and thermosetting resins.

[0021] Examples of thermoplastic resins include polyolefin resins such as polypropylene resin, polyethylene resin, poly(1-)butene resin, polypentene resin, ethylene-propylene copolymer, ethylene-butene copolymer resin, ethylene-4-methyl-1-pentene copolymer resin, ethylene-vinyl acetate copolymer resin (EVA), and ethylene-acrylic acid copolymer; and synthetic resins such as polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, polycarbonate resin, polyphenylene ether resin, (meth)acrylic resin, polyamide resin, polyvinyl chloride resin (PVC), chlorinated polyvinyl chloride resin (CPVC), novolac resin, polyurethane resin, and polyisobutylene.

[0022] Any of the above thermoplastic resins may be crosslinked or modified to the extent that the fire resistance of the resin composition is not impaired. There is no particular limitation on the method for crosslinking the resin, and examples of the method include ordinary crosslinking methods for thermoplastic resins, such as crosslinking using various crosslinking agents or peroxides, crosslinking by electron beam irradiation, etc.

[0023] Examples of the thermosetting resin include synthetic resins such as polyurethane, polyisocyanate, polyisocyanurate, phenol resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, polyimide, etc. Among these, epoxy resin is preferable.

[0024] The epoxy resin used in the present invention is not particularly limited, but is basically obtained by reacting a monomer having an epoxy group with a curing agent. Examples of the monomer having an epoxy group include difunctional glycidyl ether type, glycidyl ester type, and polyfunctional glycidyl ether type monomers.

[0025] These monomers having an epoxy group may be used alone or in combination of two or more kinds.

[0026] The curing agent may be of polyaddition type or catalyst type. Examples of polyaddition type curing agents include polyamines, acid anhydrides, polyphenols, and polymercaptans. Examples of catalyst type curing agents include tertiary amines, imidazoles, and Lewis acid complexes. The method for curing the epoxy resin is not particularly limited, and may be performed by a known method.

[0027] Examples of the elastomer include olefin-based elastomers (TPO), styrene-based elastomers, ester-based elastomers, amide-based elastomers, vinyl chloride-based elastomers, and combinations of these.

[0028] Examples of rubber materials include natural rubber, isoprene rubber, butadiene rubber, 1,2-polybutadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, chlorinated butyl rubber, ethylene-propylene rubber, ethylene-propylenediene rubber (EPDM), chlorosulfonated polyethylene, acrylic rubber, epichlorohydrin rubber, polyvulcanized rubber, non-vulcanized rubber, silicone rubber, fluororubber, urethane rubber, etc. Of these, butyl rubber is preferred.

[0029] These synthetic resins and / or rubber materials may be used alone or in combination.

[0030] Among these synthetic resins and / or rubber materials, polyvinyl chloride resins such as polyvinyl chloride resins and chlorinated polyvinyl chloride resins are preferred from the viewpoint of being able to contain a large amount of plasticizer and being excellent in kneading efficiency. Also preferred are polyolefin resins such as ethylene-vinyl acetate copolymer resins (EVA) from the viewpoint of being able to knead without applying a load to the expanded graphite, since the processing temperature can be lowered.

[0031] Thermally expandable graphite is a conventionally known substance that has the property of expanding when heated. It is a type of crystalline compound that maintains the layered structure of carbon and is produced by treating powders of natural scaly graphite, pyrolytic graphite, kish graphite, etc. with inorganic acids such as concentrated sulfuric acid, nitric acid, and selenic acid, and strong oxidizing agents such as concentrated nitric acid, perchloric acid, perchlorates, permanganates, dichromates, dichromates, and hydrogen peroxide to generate graphite intercalation compounds.

[0032] The thermally expandable graphite obtained by the above-mentioned acid treatment may be further neutralized with ammonia, an aliphatic lower amine, an alkali metal compound, an alkaline earth metal compound, or the like.

[0033] The larger the particle size (particle diameter) of the thermally expandable graphite, the greater the expansion performance and the more preferable the fire resistance. However, the larger the particle size, the more difficult it is to disperse in the matrix, and the more time is required for kneading. From the viewpoint of expansion ratio, the particle size of the thermally expandable graphite is preferably 100 μm or more, and more preferably 400 μm or more. There is no particular upper limit to the particle diameter of the thermally expandable graphite, but it is preferably 1500 μm or less, and more preferably 1000 μm or less. Since the particle size is reflected in the particle diameter of the graphite used, commercially available thermally expandable graphite is classified using a specified sieve. It can be controlled by using. The particle size of 50% of the particles passing through from the small particle side of the raw material used was taken as the average particle size. Alternatively, the particle size distribution of the thermally expandable graphite is obtained by observing a cross-section SEM (scanning electron microscope image) of the created sheet, and the particle size distribution of 50% of the particles passing through from the small particle side in the volume-based particle size distribution obtained from that can be used to determine the average particle size.

[0034] The content of the thermally expandable graphite is not particularly limited, but is preferably 10 to 500 parts by weight relative to 100 parts by weight of the matrix component, and more preferably 50 to 300 parts by weight relative to 100 parts by weight of the matrix component. If the content is 10 parts by weight or more, the volume expansion coefficient is large, and fireproof performance is exhibited that sufficiently fills the burned-out portion of a structure such as a sash, while if it is 500 parts by weight or less, mechanical strength is maintained.

[0035] When the expandable heat insulating layer is formed, the inorganic filler increases the heat capacity and suppresses heat transfer, and also acts as an aggregate to improve the strength of the expandable heat insulating layer. The inorganic filler is not particularly limited, and examples thereof include metal oxides such as alumina, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; and metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate.

[0036] In addition to these, inorganic fillers include calcium salts such as calcium sulfate, gypsum fiber, and calcium silicate; silica, diatomaceous earth, dawsonite, barium sulfate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass fiber, glass beads, silica-based balloons, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon fiber, carbon balloons, charcoal powder, various metal powders, potassium titanate, magnesium sulfate "MOS" (trade name), lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, stainless steel fiber, zinc borate, various magnetic powders, slag fiber, fly ash, dewatered sludge, etc. These inorganic fillers may be used alone or in combination of two or more.

[0037] In one embodiment, the inorganic filler is selected from metal oxides, hydrous minerals, metal carbonates, silica, and combinations thereof. Hydrous minerals include alkaline earth metal hydroxides.

[0038] As the inorganic filler, a compound having flame retardancy (flame retardant) such as a phosphorus compound may be added. The addition of the phosphorus compound increases the strength of the expandable insulation layer and improves the fireproofing performance. The phosphorus compound is not particularly limited, and examples thereof include red phosphorus; various phosphoric acid esters such as triphenyl phosphate, tricresyl phosphate (TCP), trixylenyl phosphate, cresyl diphenyl phosphate, and xylenyl diphenyl phosphate; metal salts of phosphoric acid such as sodium phosphate, potassium phosphate, and magnesium phosphate; and compounds represented by the following chemical formula (1).

[0039] [ka]

[0040] In chemical formula (1), R 1 and R 3 R represents hydrogen, a linear or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 16 carbon atoms. 2 is a hydroxyl group, carbon number 1-16 a linear or branched alkyl group having 1 to 16 carbon atoms, a linear or branched alkoxy group having 1 to 16 carbon atoms, an aryl group having 6 to 16 carbon atoms, or an aryloxy group having 6 to 16 carbon atoms.

[0041] As the red phosphorus, commercially available red phosphorus can be used, but from the standpoint of safety, such as moisture resistance and prevention of spontaneous combustion during kneading, red phosphorus particles whose surfaces are coated with a resin are preferably used.

[0042] The compound represented by chemical formula (1) is not particularly limited, and examples thereof include methylphosphonic acid, dimethyl methylphosphonate, diethyl methylphosphonate, ethylphosphonic acid, propylphosphonic acid, butylphosphonic acid, 2-methylpropylphosphonic acid, t-butylphosphonic acid, 2,3-dimethyl-butylphosphonic acid, octylphosphonic acid, phenylphosphonic acid, dioctylphenylphosphonate, dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid. Among them, t-butylphosphonic acid is expensive, but is preferred in terms of high flame retardancy. The phosphorus compounds may be used alone or in combination of two or more.

[0043] Alternatively, it may be a salt of a lower phosphoric acid, such as primary phosphoric acid, secondary phosphoric acid, tertiary phosphoric acid, metaphosphoric acid, phosphorous acid, hypophosphorous acid, etc. In this specification, the salt includes alkali metal salts such as sodium salts and potassium salts, alkaline earth metal salts such as magnesium salts and calcium salts, other metal salts such as aluminum salts, ammonium salts, etc. From the viewpoint of fire resistance, aluminum salts of phosphorous acid are preferred.

[0044] The particle size of the inorganic filler is preferably 0.5 to 200 μm, more preferably 1 to 10 μm. When the amount of inorganic filler added is small, the dispersibility greatly affects the performance, so a small particle size is preferable, but if it is 0.5 μm or more, the dispersibility is good. When the amount of addition is large, as the filling rate increases, the viscosity of the resin composition increases and the moldability decreases, but since the viscosity of the resin composition can be reduced by increasing the particle size, a large particle size is preferable, but a particle size of 100 μm or less is desirable in terms of the surface properties of the molded body and the mechanical properties of the resin composition. The particle size of 50% of the particles passing through from the small particle side of the raw material used was taken as the average particle size. In addition, the particle size distribution of the inorganic filler was obtained by observing the cross-section SEM (scanning electron microscope image) of the prepared sheet, and the particle size of 50% of the particles passing through from the small particle side in the volume-based particle size distribution obtained from the cross-section SEM (scanning electron microscope image) can also be taken as the average particle size.

[0045] In order to obtain a desired particle size, the aggregated inorganic filler may be broken down or dispersed in a solvent or the like, and then added, and the particle size may be controlled by sieving or the like.

[0046] Examples of inorganic fillers include aluminum hydroxide such as "Hijilite H-31" (manufactured by Showa Denko K.K.) with a particle size of 18 μm and "B325" (manufactured by ALCOA CORPORATION) with a particle size of 25 μm, and calcium carbonate such as "Whiten SB Red" (manufactured by Bihoku Powder Industry Co., Ltd.) with a particle size of 1.8 μm and "BF300" (manufactured by Bihoku Powder Industry Co., Ltd.) with a particle size of 8 μm.

[0047] The content of the inorganic filler is not particularly limited, but is preferably 30 to 500 parts by weight relative to 100 parts by weight of the matrix component. If the content is 30 parts by weight or more, sufficient fire retardant performance is obtained, and if it is 500 parts by weight or less, mechanical strength is maintained. The content of the inorganic filler is more preferably 40 to 350 parts by weight.

[0048] When a phosphorus compound is contained as an inorganic filler, the content of the phosphorus compound is not particularly limited, but is preferably 30 to 300 parts by weight per 100 parts by weight of the matrix component. When the content is 30 parts by weight or more, the effect of improving the strength of the expandable heat insulating layer is sufficient, and when it is 300 parts by weight or less, the mechanical strength is maintained. The content of the phosphorus compound is more preferably 40 to 250 parts by weight.

[0049] The fire-resistant resin composition of the present invention may further contain a polyphosphate as an inorganic filler. The polyphosphate also functions as a flame retardant. The polyphosphate includes ammonium polyphosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, etc. Commercially available ammonium polyphosphate products include "AP422" and "AP462" manufactured by Clariant, "Sumisafe P" manufactured by Sumitomo Chemical Co., Ltd., and "Terrage C60" manufactured by Chisso Corporation.

[0050] A preferred ammonium polyphosphate is a surface-coated ammonium polyphosphate (also called coated ammonium polyphosphate), and among the coated ammonium polyphosphates, melamine-coated ammonium polyphosphate surface-coated with melamine is described in JP-A-9-286875, and silane-coated ammonium polyphosphate surface-coated with silane is described in JP-A-2000-63562. The melamine-coated ammonium polyphosphate is (a) a melamine-coated ammonium polyphosphate having melamine added and / or attached to the surface of a powdered ammonium polyphosphate particle, (b) a coated ammonium polyphosphate having a particle surface crosslinked by an active hydrogen possessed by an amino group in a melamine molecule present in a coating layer of the melamine-coated ammonium polyphosphate particle and a compound having a functional group capable of reacting with the active hydrogen, and / or (c) a coated ammonium polyphosphate having a powdered ammonium polyphosphate or a surface coated with a thermosetting resin by the melamine-coated ammonium polyphosphate particle. Commercially available melamine-coated ammonium polyphosphate particles include, for example, "AP462" manufactured by Clariant, "FR CROS 484" manufactured by Budenheim Iberica, and "FR Examples of commercially available silane-coated ammonium polyphosphate particles include "FR CROS 486" manufactured by Budenheim Iberica.

[0051] The average particle size of the coated ammonium polyphosphate is preferably 15 to 35 μm. The average particle size of the coated ammonium polyphosphate can be measured by laser diffraction particle size distribution measurement.

[0052] In the fire-resistant resin composition of the present invention, the particle size ratio of the particle size of the thermally expandable graphite to the particle size of the inorganic filler is 1 to 1000. By setting it in this range, the thermally expandable graphite having a large particle size can be efficiently dispersed in the matrix resin without being hindered by the inorganic filler, and the inorganic filler is dispersed among the thermally expandable graphite dispersed in the resin, and the dispersion of the inorganic filler is also improved, resulting in improved kneading efficiency. The particle size ratio is preferably 3 to 500, more preferably 5 to 50. By setting it in such a numerical range, kneading can be efficiently performed in a short time. In addition, if the particle size ratio is outside this range, the dispersion of the thermally expandable graphite in the matrix is ​​insufficient, causing problems such as surface staining and variation.

[0053] In the fire-resistant resin composition of the present invention, the total content of the thermally expandable graphite and the inorganic filler is 30% by weight or more, preferably 50% by weight or more. The upper limit of the total content of the thermally expandable graphite and the inorganic filler is not particularly limited, but is 75% by weight or less, preferably 60% by weight or less. By setting the content within this range, excellent fire resistance can be achieved.

[0054] In addition, in the fire-resistant resin composition of the present invention, the content of thermally expandable graphite is 5% by weight or more, More preferably, it is 15% by weight or more, even more preferably 20% by weight or more, and most preferably 25% by weight or more. The upper limit of the content of thermally expandable graphite is not particularly limited, but is 75% by weight or less, and 50% by weight or less. By setting it in such a numerical range, excellent fire resistance can be exhibited. In a preferred embodiment of the present invention, when the matrix components are synthetic resins and elastomers, the content of thermally expandable graphite is 15% by weight or more, preferably 20% by weight or more, and more preferably 25% by weight or more. In another preferred embodiment, when the matrix component is rubber, the content of thermally expandable graphite is 5% by weight or more, preferably 15% by weight or more, more preferably 20% by weight or more, and even more preferably 25% by weight or more.

[0055] The fire-resistant resin composition of the present invention may further contain a plasticizer.

[0056] The plasticizer is added to adjust the melt viscosity of the matrix component, particularly the thermoplastic resin. The plasticizer can also be called a softener. As the plasticizer, one or a combination of two or more of the following plasticizers may be used: Phthalate plasticizers such as di-2-ethylhexyl phthalate (DOP), di-n-octyl phthalate, diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), diundecyl phthalate (DUP), or phthalates of higher alcohols or mixed alcohols having about 10 to 13 carbon atoms; aliphatic dibasic acid ester plasticizers such as di-2-ethylhexyl adipate, di-n-octyl adipate, di-n-decyl adipate, diisodecyl adipate, di-2-ethylhexyl azelate, dibutyl sebacate, and di-2-ethylhexyl sebacate; Trimellitate ester plasticizers such as tri-2-ethylhexyl trimellitate (TOTM), tri-n-octyl trimellitate, tridecyl trimellitate, triisodecyl trimellitate, and di-n-octyl-n-decyl trimellitate; Adipate plasticizers such as di-2-ethylhexyl adipate (DOA) and diisodecyl adipate (DIDA); Sebacate plasticizers such as dibutyl sebacate (DBS) and di-2-ethylhexyl sebacate (DOS); Phosphate ester plasticizers such as tributyl phosphate, trioctyl phosphate, octyl diphenyl phosphate, tributoxyethyl phosphate, trichloroethyl phosphate, tris(2-chloropropyl)phosphate, tris(2,3-dichloropropyl)phosphate, tris(2,3-dibromopropyl)phosphate, tris(bromochloropropyl)phosphate, bis(2,3-dibromopropyl)-2,3-dichloropropyl phosphate, and bis(chloropropyl)monoctyl phosphate; Biphenyltetracarboxylic acid tetraalkyl ester plasticizers such as 2,3,3',4'-biphenyltetracarboxylic acid tetraheptyl ester; Polyester polymer plasticizers; Epoxy plasticizers such as epoxidized soybean oil, epoxidized linseed oil, epoxidized cottonseed oil, and liquid epoxy resins; Chlorinated paraffins; Chlorinated fatty acid esters, such as alkyl pentachloride stearates; and Process oils such as paraffin-based process oil, naphthene-based process oil, and aromatic process oil.

[0057] The content of the plasticizer in the fire-resistant resin composition is not particularly limited, but is preferably within the range of 25 to 100 parts by weight per 100 parts by weight of the thermoplastic resin.

[0058] The fire-resistant resin composition of the present invention may further contain a heat stabilizer, a lubricant, etc., within the range that does not impair the physical properties of the composition. , processing aids, thermal decomposition type foaming agents, antioxidants, antistatic agents, pigments, etc. may also be added.

[0059] Examples of the heat stabilizer include lead heat stabilizers such as tribasic lead sulfate, tribasic lead sulfite, dibasic lead phosphite, lead stearate, and dibasic lead stearate; organotin heat stabilizers such as organotin mercapto, organotin malate, organotin laurate, and dibutyltin malate; and metal soap heat stabilizers such as zinc stearate and calcium stearate. These may be used alone or in combination of two or more.

[0060] Examples of lubricants include waxes such as polyethylene, paraffin, and montanic acid; various ester waxes; organic acids such as stearic acid and ricinoleic acid; organic alcohols such as stearyl alcohol; and amide compounds such as dimethylbisamide. These may be used alone or in combination of two or more.

[0061] Examples of processing aids include chlorinated polyethylene, methyl methacrylate-ethyl acrylate copolymers, and high molecular weight polymethyl methacrylate.

[0062] Examples of the thermal decomposition type foaming agent include azodicarbonamide (ADCA), dinitrosopentamethylenetetramine (DPT), p,p-oxybisbenzenesulfonylhydrazide (OBSH), azobisisobutyronitrile (AIBN), and the like.

[0063] The fire-resistant resin composition of the present invention can be melt-extruded in a conventional manner using an extruder such as a single-screw extruder or a twin-screw extruder to obtain a fire-resistant resin molded article. The melting temperature varies depending on the matrix component and is not particularly limited, but for example, in the case of polyvinyl chloride resin, it is 130 to 170°C.

[0064] The fire-resistant resin composition or fire-resistant resin molded body of the present invention can be used to impart fire resistance to fittings such as windows, shoji screens, doors (i.e., doors), doors, sliding doors, and transoms; ships; and structures such as elevators. The fire-resistant resin composition of the present invention has excellent moldability, so that a specially shaped molded body adapted to the complex shape of a structure can be easily obtained. FIG. 1 shows an example in which the fire-resistant resin molded body 4 of the present invention is applied to the sash frame of a window 1 as a fitting. In this example, the sash frame has two inner frames 2 and one outer frame 3 surrounding the inner frame 2, and the fire-resistant resin molded body 3 is attached inside the inner frame 2 and the outer frame 3 along each side of the frame body of the inner frame 2 and the outer frame 3. In this way, the fire-resistant resin molded body 3 of the present invention is provided to impart fire resistance to the window 1.

[0065] The present invention is not limited to the above-described embodiment, and for example, the following embodiments may also be adopted. When rubber (e.g., butyl rubber) is used as the matrix resin, the content of thermally expandable graphite is preferably 5% by weight or more and 10% by weight or less. The total content of thermally expandable graphite and inorganic filler is preferably 30% by weight or more and 70% by weight or less.

[0066] The particle size ratio between the particle size of the thermally expandable graphite and the particle size of the inorganic filler may be in the range of 1-1000, preferably 30-700, more preferably 50-200, and further preferably 65-75.

[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. EXAMPLES

[0068] 1. Making fireproof sheets [Example 1] In the amounts shown in Table 1, 100 parts by weight of polyvinyl chloride as a synthetic resin (matrix component), 80 parts by weight of diisodecyl phthalate (DIDP) as a plasticizer, 100 parts by weight of thermally expandable graphite (GREP-EG manufactured by Tosoh Corporation, particle size: 800 μm), and 50 parts by weight of aluminum phosphite (particle size: 100 μm) as an inorganic filler were mixed in a kneader, and the mixture was molded into a sheet using a calendar roll to obtain a fire-resistant sheet as a fire-resistant resin molded body with a width of 1000 mm, a thickness of 1.5 mm, and a length of 1 m. The kneading time in the kneader was standardized to 5 minutes after adding the graphite, and the test was performed.

[0069] [Examples 2 to 33 and Comparative Examples 1 to 4] For Examples 2 to 33 and Comparative Examples 1 to 4, the components were mixed in the amounts shown in Tables 1 to 3 in the same manner as in Example 1 and formed into sheets to obtain fire-resistant sheets.

[0070] 2.Fire resistance (expansion ratio) measurement From the obtained fireproof sheet, samples were taken from three points: the center and center part in front of the flow direction, and the center part in the back of the flow direction, and the prepared test pieces (length 100mm, width 100mm, thickness 1.5mm) were placed in a specified holder, fed into an electric furnace, and heated at 600℃ for 30 minutes, after which the thickness of the test piece was measured and the expansion ratio was calculated as (thickness of test piece after heating) / (thickness of test piece before heating). The difference between the minimum and maximum values ​​was marked as ◎ when it was within 5% of the average, ○ when it was within 10%, and × when it was 10% or more.

[0071] 3. Surface finish evaluation of fireproof sheets The surface finish of the fireproof sheets of Examples 1 to 10 and Comparative Examples 1 and 2 was evaluated by visually checking the surface roughness and dirt. The surface roughness (presence or absence of cracks or creases) and dirt (exposure of powder on the surface) were evaluated by visually checking. Cracks and creases are defined as having a size of 3 mm or more, and powder exposure is defined as white on the black sheet surface or an exposed area of ​​graphite of 4 mm or more. 2 The definition was "5 or less" in the created 100cm x 100cm sheet. If there were 5 or less, it was marked "○", and if there were 3 or more, it was marked "×". ○: No cracks on the surface or 5 cracks of 3 mm or more per m 2 Within ×: 5 cracks of 3 mm or more on the surface / m 2 The end.

[0072] 4. Strength evaluation The breaking strength of the obtained fireproof sheet was measured. The measurement method was based on JIS K 7161, and the tensile strength in the machine direction of the roll was measured. The sheet which broke at the time of 110% strain was marked with ×, and the sheet which did not break was marked with ◯.

[0073] The fire-resistant sheets of Examples 1 to 33 were excellent in surface finish, and deterioration of quality was suppressed.

[0074] [Table 1]

[0075] [Table 2]

[0076]

Table 3

[0077]

Table 4

Claims

1. A fire-resistant resin composition comprising a matrix component which is a resin, an elastomer, a rubber, or a combination thereof, thermally expandable graphite, and an inorganic filler, A fire-resistant resin composition, characterized in that the particle size ratio of the particle size of the thermally expandable graphite to the particle size of the inorganic filler is in the range of 1 to 1000, the total content of the thermally expandable graphite and the inorganic filler is 30% by weight or more, and the content of the thermally expandable graphite is 15% by weight or more.

2. A fire-resistant resin composition comprising a matrix component which is a resin, an elastomer, a rubber, or a combination thereof, thermally expandable graphite, and an inorganic filler, A fire-resistant resin composition, characterized in that the particle size ratio of the particle size of the thermally expandable graphite to the particle size of the inorganic filler is in the range of 1 to 1000, the total content of the thermally expandable graphite and the inorganic filler is 30% by weight or more, and the content of the thermally expandable graphite is 5% by weight or more.

3. 3. The fire-resistant resin composition according to claim 1, wherein the thermally expandable graphite has an average particle size of 100 μm or more.

4. 4. The fire-resistant resin composition according to claim 1, further comprising a phosphite as the inorganic filler.

5. The fire-resistant resin composition according to any one of claims 1 to 4, further comprising a polyphosphate.

6. The fire-resistant resin composition according to any one of claims 1 to 5, further comprising a plasticizer.

7. 7. The fire-resistant resin composition according to claim 1, wherein the matrix component is a polyvinyl chloride resin or a polyolefin resin.

8. A fire-resistant resin molding comprising the fire-resistant resin composition according to any one of claims 1 to 7.

9. A fitting comprising the fire-resistant resin molding according to claim 8.

Citation Information

Patent Citations

  • Thermally-expansible multilayer frame material for sash

    JP2013136939A

  • Chlorinated vinyl chloride resin composition for extrusion molding

    WO2013080563A1

  • Fire-resistant resin composition

    JP1997227716A

  • Chlorinated polyvinyl chloride resin composition

    JP1997227747A

  • Polyvinyl chloride resin composition

    JP1998095887A